A combined energy-bandwidth approach to allocate resilient virtual software defined networks. (July 2016) - Gomes, Rafael L.; Bittencourt, Luiz F.; Madeira, Edmundo R.M.; Cerqueira, Eduardo; Gerla, Mario
Abstract: The Internet supports many applications for millions of users every day and will enable the creation of even more innovative services for all participants. However, there is still no Quality of Service (QoS) guarantee for the users. In order to specify requirements, clients establish Service Level Agreements (SLAs) with their Internet Service Providers (ISPs), where resilience and available bandwidth are key requirements for the success of Internet services. On the other hand, the ISPs aim to maximize their profit by establishing as many SLAs as possible and decrease the energy consumption to deliver their services. The mixing of Software Defined Networks (SDNs) and Virtual Networks (VNs), called Virtual Software Defined Network (VSDN), improves the flexibility and manageability of networks, arising it as an option to achieve these goals. Within this context, this paper presents two algorithms to allocate VSDNs: (i) the Bandwidth and Reliability According to Redundancy ( BRAR ) algorithm to achieve resilience; and (ii) the Bandwidth and Energy Efficiency Focus ( BEE-Focus ) algorithm to find paths taking into account bandwidth availability and energy efficiency. The results show the benefits of the proposed algorithms in deploying resilient VSDNs regarding energy efficiency, while improving bandwidth availability in the network infrastructure.